New semisynthetic α-glucosidase inhibitor from a doubly-chemically engineered extract - María I. Osella; Mario O. Salazar; Carlos M. Solís; Ricardo L. E. Furlan (Natural Products and Bioprospecting)
Abstract Chemically engineered extracts represent a promising source of new bioactive semi-synthetic molecules. Prepared through direct derivatization of natural extracts, they can include constituents enriched with elements and sub-structures that are less common in natural products compared to drugs. Fourteen such extracts were prepared through sequential reactions with hydrazine and a fluorinating reagent, and their α-glucosidase inhibition properties were compared. For the most bioactive mixture, a chemically modified propolis extract, enzyme inhibition increased 22 times due to the reaction sequence. Bio-guided fractionation led to the isolation of a new fluorinated pyrazole produced within the extract by chemical transformation of the flavonoid chrysin. The inhibitor results from the action of the two reagents used on four common functional groups present in natural products (carbonyl, phenol, aromatic carbon, and a double bond). The reactions led to the opening of a 6-member oxygenated heterocycle to produce a 5-member nitrogenated one, as well as the dehydroxylation and fluorination in two different positions of one of the aromatic rings of the natural starting material, all within a complex mixture of natural products. Overall, these transformations led to an approximately 20-fold increase in the α-glucosidase inhibition by the isolated inhibitor compared to its natural precursor. Graphical Abstract